PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, PROFITABILITAS DAN AKTIVITAS, TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN PROPERTY, REAL ESTATE, AND BUILDING - Ni Komang Sariasih; Komang Fridagustina Adnantara; Laras Oktaviani (Journal Research of Accounting, 2021)
This study aims to determine the effect of the Liquidity Ratio, Solvency, Profitability and Activity on Dividend Policy at Property, Real Estate, and Building Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period. The reason for choosing property, real estate and building companies as objects of research is because the property sector is considered to be still an attractive investment in the midst of a new type of corona virus pandemic that causes Covid-19. Travelio Property Management Business Development Manager Vincentius Christopher considers that currently the benefits that can be taken from property investment are in terms of yield (profits calculated from the annual rental value compared to property prices), not capital gains. The population in this study are property, real estate, and building companies that already exist and are still listed on the Indonesia Stock Exchange for the 2017-2019 period, which consists of 91 companies. The sampling technique used in this study was purposive sampling so that it consisted of 87 companies as the research sample. The data analysis technique used in this study was multiple linear regression. The test results show that the liquidity ratio and profitability ratios have a significant positive effect on dividend policy, the solvency ratio has a significant negative effect on dividend policy, while the activity ratio does not have a significant effect on dividend policy.